Aumento de força muscular através de exercícios uniarticulares e multiarticulares aumenta o limiar de dor superficial e profunda em indivíduos com osteoartrite de joelho - Silva, Vanessa Martins Pereira (2016)
The main symptom of knee osteoarthritis (KOA) is pain and it could become chronic affecting superficial and deep tissues. One of the better forms for non-pharmacological treatment is the quadriceps muscle strengthening, but the best way to perform, single-joint or multi-joint exercise, and its effects over chronic pain are not known. The objective of this study was to compare the pressure pain thresholds (PPT) and the physic function (WOMAC) before and after treatment with single-joint and multi-joint exercises in individuals with KOA. Thirty individuals with KOA received treatment for quadriceps strengthening for eight weeks, and were distributed by stratified randomization in relation to sex and level of severity of KOA. One group received intervention by single-joint exercise and other group multi-joint exercise. Physic function (WOMAC) and PPT at several points in dermatomes, myotomes and sclerotomes were evaluated before and after the intervention. Both ways to muscle strengthening produced improvements in most analyzed points. The results suggest that single-joint or multi-joint exercises for muscle strengthening are effective for increase of PPT and improvement of physical function in individuals with KOA.